Septicemia due to Streptococcus dysgalactiae subspecies dysgalactiae in vampire bats (Desmodus rotundus) - Ribeiro Mioni, Mateus de Souza [UNESP]; Castro Castro, Fernando Favian; Moreno, Luisa Zanolli; Apolinario, Camila Michelle [UNESP]; Belaz, Lais Dario [UNESP]; Peres, Marina Gea [UNESP]; Davide Ribeiro, Bruna Leticia [UNESP]; Silva Castro, Maria Jose da [UNESP]; Ferreira, Adriano Martison [UNESP]; Cortez, Adriana; Moreno, Andrea Micke; Heinemann, Marcos Bryan; et al. (Nature Publishing Group, 2018)
Beta-hemolytic Streptococcus dysgalactiae is a well-known pathogen for a wide range of animals and humans. Two subspecies are recognized: (i) equisimilis, associated to disease in horses and humans, and (ii) dysgalactiae mainly isolated from animal illness with only a few humans' cases. This study describes the isolation and characterization of Streptococcus dysgalactiae subsp. dysgalactiae (SDSD) from vampire bats, maintained in captivity for research proposes. Animals presented neurologic, respiratory and gastroenteric symptoms and sudden death. Beta-hemolytic Gram-positive cocci were isolated in blood agar plates and further characterized as Lancefield group C. All isolates were identified as S. dysgalactiae by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry and subspecies dysgalactiae was confirmed by 16S rRNA sequencing and phylogenetic analysis. Genotyping through SE-ALFP resulted in three profiles (A1-A3) with one bat being infected by profiles A1 and A3. This is the first report of SDSD causing illness in bats and especially in Desmodus rotundus species.